2009
DOI: 10.1089/jmf.2008.0046
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Nitrogen Reactive Species Are Effectively Scavenged by Eucalyptus globulus Leaf Water Extract

Abstract: Eucalyptus globulus Labill. (Family Myrtaceae) is a plant of Australian origin, with a reported therapeutic use in airway inflammatory diseases. Considering that reactive oxygen species (ROS) and reactive nitrogen species (RNS) have been implicated in the pathogenesis of airway inflammatory diseases such as asthma and chronic obstructive pulmonary disease, an effective scavenging activity against these reactive species may contribute for the therapeutic effect of this plant. In the present study, a water extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
5
30
0
2
Order By: Relevance
“…Quercetin showed an IC 50 of 0.5 lg/mL. The IC 50 values of these extracts showed better efficiency as 1 O 2 quenchers than extracts from Juglans regia leaves (Almeida et al, 2008a), Castanea sativa, Quercus robur (Almeida et al, 2008b), Hypericum androsaemum (Almeida, Fernandes, Lima, Costa, & Bahia, 2009) and Eucalyptus globulus leaf water extract (Almeida, Fernandes, Lima, Valentão, et al, 2009). As expected, bixin showed lower IC 50 than all annatto extracts.…”
Section: Scavenging Of Ros and Rns By Annatto Extractssupporting
confidence: 57%
See 2 more Smart Citations
“…Quercetin showed an IC 50 of 0.5 lg/mL. The IC 50 values of these extracts showed better efficiency as 1 O 2 quenchers than extracts from Juglans regia leaves (Almeida et al, 2008a), Castanea sativa, Quercus robur (Almeida et al, 2008b), Hypericum androsaemum (Almeida, Fernandes, Lima, Costa, & Bahia, 2009) and Eucalyptus globulus leaf water extract (Almeida, Fernandes, Lima, Valentão, et al, 2009). As expected, bixin showed lower IC 50 than all annatto extracts.…”
Section: Scavenging Of Ros and Rns By Annatto Extractssupporting
confidence: 57%
“…The IC 50 values for all the tested extracts in this study showed better capacity than other extracts found in the literature, such as medicinal tincture from J. regia leaf extract (Almeida et al, 2008a), C. sativa and Q. robur (Almeida et al, 2008b), H. androsaemum (Almeida, Fernandes, Lima, Costa, et al, 2009), E. globulus (Almeida, Fernandes, Lima, Valentão, et al, 2009) and Pedilanthus tithymaloides (Abreu et al, 2006). The H 2 O 2 scavenging capacity of all annatto extracts analysed in this study was also better than that of quercetin (245 lg/mL), tested in the same conditions, ascorbic acid (200 lg/mL) (Abreu et al, 2006;Almeida et al, 2008aAlmeida et al, , 2008bAlmeida, Fernandes, Lima, Costa, et al, 2009;Almeida, Fernandes, Lima, Valentão, et al, 2009).…”
Section: Scavenging Of Ros and Rns By Annatto Extractsmentioning
confidence: 47%
See 1 more Smart Citation
“…The efficiency of ethanol/water and water extracts in the scavenging capacity against Å NO was higher than that of Pedilanthus tithymaloides medicinal tincture (Abreu et al, 2006), extracts of seeds, stems, leaves and petals of Catharanthus roseus (Ferreres et al, 2008), extracts of Sesamum indicum seeds (Visavadiya, Soni, & Dalwadi, 2009) and annatto seed extracts (Chisté et al, 2011). Additionally, the IC 50 values of ethanol/water and water extracts, for Å NO-scavenging properties, were similar to the other plant extracts, such as Juglans regia (Almeida et al, 2008a), C. sativa, Q. robur (Almeida et al, 2008b), H. androsaemum (Almeida, Fernandes, Lima, Costa, et al, 2009) and Eucalyptus globulus (Almeida, Fernandes, Lima, Valentão, et al, 2009). On the other hand, the extracts of C. villosum obtained with ethanol, ethanol/ethyl acetate and ethyl acetate, which presented the highest carotenoid contents and the lowest phenolic levels, were the least effective in scavenging Å NO (Fig.…”
Section: åàmentioning
confidence: 72%
“…The H 2 O 2 -scavenging capacity of ellagic acid (IC 50 of 108.3 lg/ml) was higher than that of gallic acid (226 lg/ml) and that of quercetin (290 lg/ml); however, it was lower than that of ascorbic acid (Abreu et al, 2006;Almeida, Fernandes, Lima, Costa, & Bahia, 2008a, 2008b, 2009aAlmeida, Fernandes, Lima, Valentão, et al, 2009). H 2 O 2 alone is practically harmless, whereas it may spread easily through the cell membranes, for example, the membrane of the nucleus, and can react with transition metals (Cu + and Fe 2+ ) inside cells (Fenton reaction) to generate the most reactive ROS, namely hydroxyl radical (HO Å ).…”
Section: åàmentioning
confidence: 88%